2003
DOI: 10.1096/fj.02-0941fje
|View full text |Cite
|
Sign up to set email alerts
|

A novel calcium‐dependent proapoptotic effect of annexin 1 on human neutrophils

Abstract: The glucocorticoid-inducible protein annexin (ANXA) 1 is an anti-inflammatory mediator that down-regulates the host response. Endogenously, ANXA1 is released in large amounts from adherent polymorphonuclear neutrophils (PMN) and binds to their cell surface to inhibit their extravasation into inflamed tissues. The present study determined the effects of exogenous ANXA1 on several functions of human PMN in vitro. Addition of 0.1-1 microM human recombinant ANXA1 to the PMN provoked rapid and transient changes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
162
0
7

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(179 citation statements)
references
References 66 publications
10
162
0
7
Order By: Relevance
“…This allows BAD to associate with mitochondria, heterodimerize with Bcl-XL and promote apoptosis. 4 The present data support the hypothesis that in FRO cells ANXA1 may promote apoptosis by reducing the phosphorylation levels of Bad. No evidence is currently available as to which phosphatase, if any, might be activated by ANXA1 to dephosphorylate Bad.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…This allows BAD to associate with mitochondria, heterodimerize with Bcl-XL and promote apoptosis. 4 The present data support the hypothesis that in FRO cells ANXA1 may promote apoptosis by reducing the phosphorylation levels of Bad. No evidence is currently available as to which phosphatase, if any, might be activated by ANXA1 to dephosphorylate Bad.…”
supporting
confidence: 87%
“…Conversely, a remarkable ANXA1 expression on FRO cell membrane was observed at 24 h after TRAIL ( Figure 1c). As ANXA1 may induce apoptosis through Bad dephosphorylation, 4 the levels of both Bad and phospho-Bad proteins were measured by Western blot after TRAIL stimulation. Figure 1c shows that phospho-Bad levels decreased with time and were barely detectable at 24 h after TRAIL.…”
mentioning
confidence: 99%
“…Several of these genes may have roles in processes such as growth control, maintenance of genome integrity, apoptosis and cancer. ANXA1 (ANNEXIN 1) is a member of the annexin family of calcium-and phospholipid-binding proteins and has proapoptotic effect in circulating neutrophils 15 and rat thymo- cytes. 16 The observation that ANXA1 is expressed on the cell surface suggests that it may constitute an 'eat me' signal for removal of apoptotic cells.…”
Section: Discussionmentioning
confidence: 99%
“…Evidences have been showed that annexin A1 mediates various important physiologic processes depending on its subcellular localization in vitro and in vivo in a variety of human malignancies. For instance, at intracellular level, annexin A1 can interact with the cytosolic form of phospholipase A2 (cPLA2) and cyclooxygenase 2 (COX-2) to block enzyme activity (Kim et al, 1994;Hannon et al, 2003), and annexin A1 can mediate apoptosis by inducing the dephosphorylation of BAD, allowing BAD to translocate to the mitochondria, whereas annexin A1 itself translocates to the nucleus (Solito et al, 2003a), however, the mechanism and functional relevance of annexin A1 nuclear localization is still unknown, and annexin A1 also can be phosphorylated by EGF-R tyrosine kinase, protein kinase C (PKC), platelet-derived growth factor receptor tyrosine kinase (PDGFR-TK), and hepatocyte growth factor receptor tyrosine kinase (HGFR-TK) to mediate proliferation (Lim & Pervaiz., 2007); at the external membrane level, annexin A1 acts as a negative regulator of inflammatory process, including blocking the rolling of polymorphonuclear leukocyte on endothelial cells (Perretti et al, 1996), and also acts on its receptor, identified as the fomyl peptide receptor (FPR) and the formyl peptide receptor like-1 (FPRL1), to inhibit cell adhesion and migration, as well as inducing detachment of adherent cells (Rescher et al, 2002). Moreover, it can be phosphorylated and translocated to membrane by glucocorticosteroid through PKC (protein kinase C), PI3K, MAP kinase (mitogen activated protein kinase) and Ca2+ dependent pathways (Solito et al, 2003b), and binds to phosphatidylserine to mediate the engulfment of apoptotic cells when recruited to the cell surface (Arur et al, 2003).…”
Section: 4707 Prognostic Significance Of Annexin A1 Expression In Pamentioning
confidence: 99%